1992
DOI: 10.1159/000126209
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β and Interleukin-6 Specifically Increase the Release of Prostaglandin E<sub>2</sub> from Rat Hypothalamic Explants in vitro

Abstract: It has previously been shown that the cytokines interleukin-1β and interleukin-6 (IL-1β and IL-6) stimulate directly the release of corticotrophin-releasing-hormone-41 from the rat hypothalamus in vitro, while IL-1β can also stimulate the release of somatostatin. These effects can be antagonized by drugs which block prostaglandin (PG) synthesis. PGs are also involved in the control of hypothalamic neuropeptides by other neuron transmitters. In the present study, we have characterized the production of PGs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…These results are in accordance with our previous work showing that LPS induces PGE2 synthesis in rat cortical slices [7], Further more. previous findings showing that IL-1 can increase PGE2 production in hypothalamic explants [14] and with other experiments have shown that intravenous injection of IL-1 in conscious rats caused a pronounced increase in brain PGE2 in the organum vasculosum of the lamina terminalis, dorsal hippocampus and hypotha lamic paraventricular nucleus, as measured by microdia lysis [13,33].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These results are in accordance with our previous work showing that LPS induces PGE2 synthesis in rat cortical slices [7], Further more. previous findings showing that IL-1 can increase PGE2 production in hypothalamic explants [14] and with other experiments have shown that intravenous injection of IL-1 in conscious rats caused a pronounced increase in brain PGE2 in the organum vasculosum of the lamina terminalis, dorsal hippocampus and hypotha lamic paraventricular nucleus, as measured by microdia lysis [13,33].…”
Section: Discussionsupporting
confidence: 52%
“…The functional impor tance of PG production in the brain has not been fully such as bacterial endotoxin (lipopolysaccharide, LPS) and cvtokines can activate the synthesis of PG in brain tissue [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…6 -8 Many lines of evidence have confirmed that these cytokines have effects mediated via stimulation of the prostanoid cascade within the CNS. IL-6 induces fever through formation of prostanoids in rats 23 and stimulates production of PGE 2 in the rat hypothalamus 24 and cerebral arteries. 25 We also demonstrated that the concentration of PGE 2 in CSF becomes elevated over preinjection concentrations by 4.5 hours after intracisternal injection of IL-6 (data not shown), in accordance with the findings of Dinarello et al 26 The effect of IL-1␤ on the production of eicosanoids by endothelial cells is more potent than that of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…The exact PG subtype(s) and the site(s) of action involved in these effects still remain unclear, but a large body of evidence indicates that PG of E 2 type is a key molecule in the transfer of information received from circulating cytokines and foreign materials to parenchymal cells of the brain. IL-1 increases the release of PGE 2 from rat hypothalamic explants in vitro 33 and numerous regions of the brain in vivo, including the paraventricular nucleus of the hypothalamus (PVN). 34 Intracerebral administration of PGE 2 elevates plasma ACTH and corticosterone 35,36 and causes a selective cellular activation as indicated by the rapid and transient expression of the immediateearly gene (IEG) c-fos mRNA and its protein product within multiple regions of the brain recognized to be activated during the acute-phase response.…”
Section: What Are the Functional Consequences Of Pg Production By Celmentioning
confidence: 99%